Chinese medical drugs for coronavirus disease 2019: A systematic review and meta-analysis - Pang, Wentai (Integr Med Res, 2020)
BACKGROUND: Integration of Chinese medical drugs (CMD) and western medicine (WM) has been widely used in the treatment of Coronavirus Disease 2019 (COVID-19). This systematic review aimed to evaluate the efficacy and safety of CMD for COVID-19. METHOD: A literature search was performed in six databases from injection to June 2020. Both randomized controlled trials (RCTs) and quasi-RCTs were considered as eligible. The quality of included RCTs were assessed by Cochrane Risk of Bias Tool, and Review Manager 5.3 software was used to do meta-analysis. RESULT: Eleven studies with 1259 patients were included in this study. CMD included herbal decoction and Chinese patent medicine. The methodological quality was evaluated as generally unclear. The results of meta-analysis showed that the integration of CMD and WM had better efficacy than WM in number of patients turned to severe and critical type (RR = 0.47, 95% CI=[0.32, 0.69], P < 0.0001), length of hospital stay (MD= -7.95, 95% CI=[-14.66, -1.24], P = 0.02), defervescence time (MD= -1.20, 95% CI=[-2.03, -0.38], P = 0.004), cough resolution rate (RR = 1.37, 95% CI=[1.15, 1.64], P = 0.0004), fatigue resolution rate (RR = 1.37, 95% CI=[1.02, 1.83], P = 0.04), and tachypnea resolution rate (RR = 2.20, 95% CI=[1.11, 4.39], P = 0.02). As for safety, there was no significant difference between two groups. CONCLUSION: CMD may bring potential benefit to patients suffered from COVID-19. However, the quality of included trials is not good enough. High quality study with core outcome set are still required.